O canal de crédito na transmissão de política monetária: evidências para o Brasil - Sato, Carolina Yumi (2013)
This paper presents empirical evidences for the credit channel in Brazil based on Holtemöller’s (2002) previous work. For that matter, it was made a descriptive analysis on Brazilian credit evolution and econometric tests using monetary, credit and real economy data. It is possible to observe rising credit importance in the last years, as well as improving corporate financing through issuances in asset markets. Therefore, one could expect greater significance of bank lending channel in the monetary policy transmission mechanism. However, empirical analysis indicates that its effects on economic activity are restricted. After estimating the interest rate channel using vector autoregressive models, we have included credit variables to evaluate its impacts on output. Despite concluding that monetary policy shocks do have effects on loan supply, the impacts of restrictive credit conditions on industrial production is limited. Some specific characteristics of Brazilian economy are presented in the attempt to try to justify this result.